The role of women in family economic development - Zalmi, Ibrahim Haji; Younis, Sarko (Sulaimani Journal for Humanities, 2026)
Talking about the family in the process of economic development in a society like Kurdistan is a current need, because Kurdish society is in a time of change and its institutions have changed The family is an important example of the institutions of society. Objective of the study: To know the role of women in family economic development. Also knowing the role of family education in economic development in Kurdish society. This research is a field research, generally used descriptive analytical method, survey form (Istbian) was used. Research Society of Women Employees in Government Institutions of the Kurdistan Region, in which women employees in Halabja province were deliberately recruited according to the offices, (100) women were recruited as a sample. The most notable results of this study are: 1. Women employees have their own income and financial independence due to their salaries and jobs. They rely on themselves to meet their needs to a good extent. Most of them invest their money. 2. The tenancy rate among the employees is high. 3. The dominance of patriarchal social traditions and culture in Kurdish society has an impact on women's economic independence and income management, which has reduced the role of women in the economic development of the family. 4. Women employees usually have scientific degrees and are aware of the education of their children and are a good financial support for their husbands' finances and meet the needs of their families together.
Keywords: Family; Women; Development; Economic Development